Ticking ecological time bombs: Risk characterisation and management of oil polluting World War II shipwrecks in the Pacific Ocean. (March 2021) - Carter, Matthew; Goodsir, Freya; Cundall, Peter; Devlin, Michelle; Fuller, Sascha; Jeffery, Bill; Hil, Greg; Talouli, Anthony
Abstract: The Second World War in the Pacific has left a legacy of over 3800 wrecks on the ocean floor. These wrecks contain thousands of tons of oil and pose a risk to the marine environment. Estimates of current corrosion rates show many wrecks are at risk of structural collapse. However, the scale of threat posed by potentially polluting wrecks (PPW) to coastal ecosystems in the Pacific is largely unknown, due to the lack of data to inform risk. This paper presents a strategy aimed to prioritise, manage, and mitigate negative effects of oil spills posed by PPW in the Pacific, using an example in Chuuk Lagoon. Wrecks are assessed and prioritised by means of risk characterisation. Wrecks are surveyed using photogrammetry to assess hull integrity. Finally, recommendations are made for the production of bespoke management plans and risk reduction strategies that work towards safeguarding marine ecosystems and the livelihoods of coastal communities. Highlights: Large amounts of toxic oil remain hidden within legacy WWII shipwrecks. Disaster risk reduction strategy for reducing oil pollution threat in Chuuk Lagoon. Combines robust scientific data and cutting-edge technology to assess risk. Educate and mobilise the public, stakeholders and policymakers towards preparedness. Wreck specific management plans for building resilience in aquatic ecosystems.